Examining mindfulness-based stress reduction: Perceptions from minority older adults residing in a low-income housing facility - Szanton, Sarah L (BioMed Central, 2011)
BACKGROUND: Mindfulness-based stress reduction (MBSR) programs are becoming increasingly common, but have not been studied in low income minority older populations. We sought to understand which parts of MBSR were most important to practicing MBSR members of this population, and to understand whether they apply their training to daily challenges. METHODS: We conducted three focus groups with 13 current members of an MBSR program. Participants were African American women over the age of 60 in a low-income housing residence. We tape recorded each session and subsequently used inductive content analysis to identify primary themes. RESULTS AND DISCUSSION: Analysis of the focus group responses revealed three primary themes stress management, applying mindfulness, and the social support of the group meditation. The stressors they cited using MBSR with included growing older with physical pain, medical tests, financial strain, and having grandchildren with significant mental, physical, financial or legal hardships. We found that participants particularly used their MBSR training for coping with medical procedures, and managing both depression and anger. CONCLUSION: A reflective stationary intervention delivered in-residence could be an ideal mechanism to decrease stress in low-income older adult's lives and improve their health.